2020
DOI: 10.1016/j.genhosppsych.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, coping behaviors, and preferences for support among New York healthcare workers during the COVID-19 pandemic

Abstract: The mental health toll of COVID-19 on healthcare workers (HCW) is not yet fully described. We characterized distress, coping, and preferences for support among NYC HCWs during the COVID-19 pandemic. Methods: This was a cross-sectional web survey of physicians, advanced practice providers, residents/fellows, and nurses, conducted during a peak of inpatient admissions for COVID-19 in NYC (April 9th-April 24th 2020) at a large medical center in NYC (n = 657). Results: Positive screens for psychological symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

91
944
16
66

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 875 publications
(1,117 citation statements)
references
References 28 publications
91
944
16
66
Order By: Relevance
“…In a national examination of the general public, Palsson, Ballou, and Gray (2020) concluded that over half of their sample reported having higher stress levels as a result of COVID-19. As well, these findings are somewhat consistent with the afore-referenced literature related to other professional groups, such as healthcare professionals (e.g., Shechter et al, 2020 ). In addition to professional challenges, child welfare practitioners may be coping with personal challenges, such as homeschooling, caregiving, economic uncertainty, and the like, that may impact their professional roles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a national examination of the general public, Palsson, Ballou, and Gray (2020) concluded that over half of their sample reported having higher stress levels as a result of COVID-19. As well, these findings are somewhat consistent with the afore-referenced literature related to other professional groups, such as healthcare professionals (e.g., Shechter et al, 2020 ). In addition to professional challenges, child welfare practitioners may be coping with personal challenges, such as homeschooling, caregiving, economic uncertainty, and the like, that may impact their professional roles.…”
Section: Discussionsupporting
confidence: 90%
“…However, research conducted in other areas illustrate the impact of COVID-19 on an array of practitioners. For instance, in a cross-sectional study of physicians, advanced practice providers, residents/fellows, and nurses, Shechter et al (2020) found that nearly 60% of participants reported acute stress and nearly half of the sample exhibited symptoms for depressive disorder related to COVID-19. Lai et al, 2020 , Xiao et al, 2020 reached similar conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[35,37,38] No studies have reported patterns of meditation practice but one cross-sectional study assessing stress coping behaviors conducted in New York City based health care workers during COVID-19 reported that meditation (23%) was a commonly endorsed behavior, along with physical activity/exercise (59%). [52] However, physical activity and meditation patterns were not assessed prior to COVID-19. More research describing patterns of health behaviors during COVID-19 is needed to better understand how COVID-19 may contribute to long-lasting, negative health behavior changes.…”
Section: Mental Health and Perceptions Of Covid-19 By Regionmentioning
confidence: 99%
“…Healthcare providers working on the frontlines and in general wards were all exposed to various COVID-19-related stressors [ 15 ]. These unprecedented COVID-19-related stressors were associated with adverse psychological consequences among healthcare providers [ 16 , 17 ]. Quantitative studies have shown that frontline healthcare providers treating COVID-19 patients were vulnerable to higher risks of mental health problems, such as anxiety, depression, and insomnia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing COVID-19 studies have documented various coping behaviors in response to the COVID-19 pandemic among healthcare providers. The results from a US study showed that 80% of healthcare providers adopted at least one type of coping behavior to manage COVID-19-related stress, with physical activity/exercise being the most commonly endorsed behavior [ 17 ]. In addition, self-care as one type of coping behavior was extremely vital to minimize potential adverse long-term effects from COVID-19.…”
Section: Introductionmentioning
confidence: 99%